Human Herpesvirus 6 and Malignancy: A Review - Eliassen, Eva; Lum, Emily; Pritchett, Joshua; Ongradi, Joseph; Krueger, Gerhard; Crawford, John R.; Phan, Tuan L.; Ablashi, Dharam; Hudnall, Stanley David (Frontiers in Oncology, 2018)
In order to determine the role of human herpesvirus 6 (HHV-6) in human disease, several confounding factors, including methods of detection, types of controls, and the ubiquitous nature of the virus, must be considered. This is particularly problematic in the case of cancer, in which rates of detection vary greatly among studies. To determine what part, if any, HHV-6 plays in oncogenesis, a review of the literature was performed. There is evidence that HHV-6 is present in certain types of cancer; however, detection of the virus within tumor cells is insufficient for assigning a direct role of HHV-6 in tumorigenesis. Findings supportive of a causal role for a virus in cancer include presence of the virus in a large proportion of cases, presence of the virus in most tumor cells, and virus-induced in-vitro cell transformation. HHV-6, if not directly oncogenic, may act as a contributory factor that indirectly enhances tumor cell growth, in some cases by cooperation with other viruses. Another possibility is that HHV-6 may merely be an opportunistic virus that thrives in the immunodeficient tumor microenvironment. Although many studies have been carried out, it is still premature to definitively implicate HHV-6 in several human cancers. In some instances, evidence suggests that HHV-6 may cooperate with other viruses, including EBV, HPV, and HHV-8, in the development of cancer, and HHV-6 may have a role in such conditions as nodular sclerosis Hodgkin lymphoma, gastrointestinal cancer, glial tumors, and oral cancers. However, further studies will be required to determine the exact contributions of HHV-6 to tumorigenesis.